Example of the use of surface electromyography to evaluate throws in softball - Süss, Vladimír; Kračmar, Bronislav; Süss, Vladimír (Acta Universitatis Carolinae. Kinanthropologica, 2006)
Purpose of this study is shown differences in internal structure two overhead throw, that are submission to the methodical series training softball throwing. Record study denotes validity election method Surface Electromyography (SEMG) for description wiring muscular strings in overhead throw. Be under examination muscular descriptor with those muscles (except m. tensor fascia latae sin. all right-side): 1 m. pectoralis major – pars sternocostalis, 2. m. abdominis externus, 3. m tensor fascia latae, 4. m. latissimus dorsi, 5. m. serratus anterior, 6. m. trapezius – pars tranversa. Records reflect that that method it is possible find next differences in throw.
Keywords: financování organizované; dospělí; Statistics as Topic; Movement; statistika jako téma; pohyb; Adult; sporty; Athletic Performance; postura těla; lidé; Kinesiology, Applied; baseball; Humans; Electromyography; Financing, Organized; biomechanika; Male; Sports; Posture; sportovní výkon; mužské pohlaví; Baseball; Biomechanical Phenomena; elektromyografie; kineziologie aplikovaná